2022
DOI: 10.3390/su14063291
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Trade Liberalization and Nutrition Intake for Improving Food Security across Districts in Indonesia

Abstract: The debate on the effect of trade liberalization on food security poses solid arguments, both in favor as well as against the issue. This study aims to analyze the linkages between trade liberalization (measured using food import tariff exposure) and food security (measured using nutrition intake) in the case of Indonesia. The national food import tariff is decomposed into district-level import tariff exposure and is analyzed based on sectoral tariffs such as agriculture tariffs and food manufacture import tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 22 publications
(26 reference statements)
1
17
1
1
Order By: Relevance
“…Ceteris paribus, as the food import tariffs decrease by 1%, on average, the inequality of calorie intake increased by 0.45, the inequality of zinc intake by 0.56, the inequality of vitamin B 1 intake by 0.48, and the inequality of vitamin B 2 by 0.66. Existing research suggested that increased food trade openness would logically increase the number of calories and nutrients available [ 9 , 36 ]. However, our findings imply that those who need it most (living mostly in rural areas) may not benefit from increased food trade and that inequalities in nutrition consumption do not improve as a result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceteris paribus, as the food import tariffs decrease by 1%, on average, the inequality of calorie intake increased by 0.45, the inequality of zinc intake by 0.56, the inequality of vitamin B 1 intake by 0.48, and the inequality of vitamin B 2 by 0.66. Existing research suggested that increased food trade openness would logically increase the number of calories and nutrients available [ 9 , 36 ]. However, our findings imply that those who need it most (living mostly in rural areas) may not benefit from increased food trade and that inequalities in nutrition consumption do not improve as a result.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that reductions in tariffs due to trade liberalization would exacerbate inequality in the consumption of calories, zinc, vitamin B 1, and vitamin B 2 (Table 2 ). Food trade liberalization is often considered as a core element aiming to improve national malnutrition [ 36 ]. However, most developing countries are not competitive enough to take advantage of the positive impact of trade liberalization on nutrition consumption, which is closely linked to income distribution, the performance of national food markets, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This resonates with the broader study on the impact of globalization on food security in Sub-Saharan Africa, emphasizing the interconnectedness of economic factors and agricultural outcomes. Montolalu et al (2022) analysis of trade liberalization and dietary consumption in diverse Indonesian districts reveals a negative relationship between import tariff exposure and nutritional intake, varying across economic sectors and geographic regions within Indonesia. The study underscores the importance of considering regional specifics, economic conditions, and employment factors when implementing trade policies.…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…Succinctly put, food security has been a major concern for scholars around the world and many research works published testify to this, few of them being Khan et al (2014) and Ayanlade and Radeny (2020). There have been very few recent empirical studies that have focused on the nexus between globalization and food security (Mary, 2019;Fusco et al, 2020;Montolalu et al, 2022). Consequently, the gap in food security literature is the unavailability of adequate empirical literature which focuses on uncovering the effect of globalization on food security in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of food is indeed an issue that continues to be discussed by the government, both about imports, selfsufficiency, and food security [9]. Especially Indonesia, as an agricultural country with fertile soil and abundant resources, is still struggling with food supply problems [10]. Indonesia itself ranks 5th on food security scores from 10 countries in ASEAN.…”
Section: Introductionmentioning
confidence: 99%